THE PRACTICAL IMPORTANCE OF AN INTEGRATIVE APPROACH TO TEACHING ASTRONOMY FROM A SMALL SCHOOL AGE (Uzbek Scholar Journal, 2024)
To date, traditional teaching has been replaced by personality-oriented approaches. From this point of view, it should be noted that the end of the 20th century paved the way for the beginning of a humanitarian culture, putting an end to technocratic progress. The exchange of the logic of power and fear for the philosophy of mind and love is a unique strategy of the XXI century.